Environmental impacts of the Vanadium redox-flow batteries - Sillberg, Oona (My University, 2024)
Vanadium redox-flow batteries (VRFB) is one of the most promising large-scale energy storage technologies for integrating renewable energy in electrical grids. They help to resolve global energy and environmental issues. In recent years, scientists are studying the degree of sustainability of this technology and its effects on the environment. In this bachelor´s thesis the environmental impacts of VRFB are discussed. Resources, recycling and reuse processes, disposal and emissions are taken into consideration and two electrolyte rebalancing methods are presented to extend the lifetime of the electroactive material. The entire lifecycle of the VRFB, from manufacturing to end-of-life phase, shows that VRFB have a great potential to reduce environmental impacts with efficient recycling and reuse of its materials. Also, a comparative analysis to lithium-ion batteries is done and the role of VRFB in the energy industry is discussed. LIBs are more suitable for portable electronic applications, and VRFBs are better for stationary energy storage. Finally, a homemade analytical system is introduced to in operando measure the gases (by gas chromatography) evolved from laboratory scale VRFBs operated under accelerated stress testing conditions.

Vanadium virtausakut ovat yksi lupaavimmista suuren mittakaavan energian varastointi teknologioista, jonka avulla uusiutuvaa energiaa voidaan integroida sähköverkkoon. Ne auttavat ratkomaan maailmanlaajuisia energia- ja ympäristöongelmia. Teknologiaa ja sen ympäristövaikutuksia on tutkittu paljon viime vuosina. Tässä kandidaatin tutkielmassa keskustellaan vanadium virtausakkujen ympäristövaikutuksista. Resurssit, kierrätys- ja uudelleenkäyttöprosessit, loppusijoitus sekä päästöt ovat huomioitu. Kaksi elektrolyytin tasapainotus metodia esitetään, joiden avulla elektroaktiivisen materiaalin elinikää voidaan pidentää. Koko vanadium virtausakun elinkaari, valmistuksesta elinkaaren loppuvaiheeseen osoittaa, että sillä on hyvä potentiaali vähentää ympäristövaikutuksia kiinnittämällä huomio tehokkaaseen kierrätykseen ja materiaalien uusiokäyttöön. Vanadium virtausakkujen ominaisuuksia sekä ympäristövaikutuksia verrataan litiumioni akkuihin ja keskustellaan virtausakkujen roolista energiasektorilla. Litiumakut soveltuvat paremmin monipuolisiin elektroniikan sovellutuksiin ja vanadium virtausakut sopivat paremmin pysyvään energian varastointiin. Lopuksi esitetään kokeellinen menetelmä, jossa laboratoriotason vanadium virtausakkuja testataan nopeutettujen olosuhteiden alaisuudessa ja mitataan syntyviä kaasuja kaasukromatografian avulla.
Keywords: vanadium redox-flow battery, VRFB, flow battery, environment, energy storage, vanadium virtausakku, virtausakku, ympäristö, energian varastointi